EFEKTIVITAS PELAYANAN PRIMA SEBAGAI UPAYA MENINGKATKAN PELAYANAN DI RUMAH SAKIT (PERSPEKTIF PSIKOLOGI) - M Noor Rochman Hadjam (Faculty of Psychology, Universitas Gadjah Mada, 2001)
This research brought to see the efectivity of services given by nurses before and after receiving services excellent skill training. This research used servises excellent quality scale which reveals quality of services excellent of the subjects that based on the theory of Sugiarto (1999). This research consist of three phases. First, subjects fill the servises excellent quality scale then wechoose 18 subjects who had lowest scores. Second, those 18 subjects were separated in two groups, control group and experiment group. Experiment group was given services excellent training for three days. Third, 18 subjects fill the servises excellent quality scale once again. The data obtained was analyzed statistically use t-test to examine the differences of services excellent of the nurses between before and after receiving service excellent training.The results shows there is a significan difference of service excellent of the nurses (t=2,65; p=0,29) between before and after receiving service excellent training. The conclusion from this research is that service excellent training is effective enough to increase the quality of services excellent of the nurse at thehospital.